Effects of acupuncture versus cognitive behavioral therapy on brain-derived neurotrophic factor in cancer survivors with insomnia: an exploratory analysis. Issue 6 (December 2021) - Liou, Kevin T; Garland, Sheila N; Li, Q Susan; Sadeghi, Keimya; Green, Jamie; Autuori, Isidora; Orlow, Irene; Mao, Jun J
Introduction: Decreased brain-derived neurotrophic factor (BDNF) is associated with poor sleep. This study examined the effects of acupuncture versus cognitive behavioral therapy for insomnia (CBT-I) on serum BDNF and sleep outcomes in cancer survivors with insomnia. Methods: This was an exploratory analysis of a randomized clinical trial (n = 160) comparing acupuncture versus CBT-I for cancer survivors with insomnia. Interventions were delivered over 8 weeks. Outcomes were assessed at baseline and week 8. Serum BDNF was evaluated with enzyme-linked immunosorbent assay (ELISA). Sleep was evaluated with the insomnia severity index and consensus sleep diary. Pearson correlations between BDNF and sleep outcomes were calculated. Data analysis was limited to 87 survivors who provided serum samples. Results: Among 87 survivors, the mean age was 61.9 (SD: 11.4) years, 51.7% were women, and 24.1% were non-White. Mean serum BDNF did not significantly increase in acupuncture (n = 50) or CBT-I (n = 37) groups. When analysis was restricted to patients with low baseline BDNF (i.e. levels below the sample median of 47.1 ng/mL), the acupuncture group (n = 22) demonstrated a significant 7.2 ng/mL increase in mean serum BDNF (P = 0.03), whereas the CBT-I group (n = 21) demonstrated a non-significant 2.9 ng/mL increase (P = 0.28). Serum BDNF was not significantly correlated with sleep outcomes (all P > 0.05). Conclusion: Among cancer survivors with insomnia and low baseline BDNF, acupuncture significantly increased serum BDNF levels; however, the clinical significance of this finding requires further investigation. Trial registration no. NCT02356575 (ClinicalTrials.gov)